EVALUATION OF PHYTOCHEMICAL ACTIVITIES OF AQUEOUS AND ETHANOLIC GARLIC PEEL EXTRACT - Fortunata, Stacia Andani; Rahmawati, Della; Andika, Dylan (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2019)
Garlic plant has been known to have various beneficial properties beside as a condiment. However, the garlic peel is still considered as waste and the research of its functional properties are still very limited. The purpose of this study was to explore the potential phytochemical activities of garlic peel extract which might be utilized as natural food additive or even functional ingredient in the future. The experiment was divided to two phases. The first phase identifies and compares the phytochemical content and activities between aqueous and ethanolic extract. The presence of saponins was detected along with the absence of alkaloids on both aqueous and ethanolic extract. The aqueous extract possessed lower flavonoid content, higher phenolic content and stronger antioxidant activity compared to the ethanolic peel extract. Ethanolic extract did not exhibit any antimicrobial activity against S.cerevisiae, while aqueous extract showed the activity against S.cerevisiae. Moreover, both types of extract also did not show any ?-glucosidase inhibition activity. In the second phase, optimization attempts for extraction method were done and it was found that the highest amount of antioxidant activity along with flavonoid and phenolic content could be obtained by changing the raw material-solvent ratio to 20 gr/1000ml.